Red flags to screen for vertebral fracture in patients presenting with low‐back pain - Williams, Christopher M.; Henschke, Nicholas; Maher, Christopher G.; Tulder, Maurits W. van; Koes, Bart W.; Macaskill, Petra; Irwig, Les (The Cochrane database of systematic reviews, 2013)
Background: Low-back pain (LBP) is a common condition seen in primary care. A principal aim during a clinical examination is to identify patientswith a higher likelihood of underlying serious pathology, such as vertebral fracture, who may require additional investigation and specifictreatment. All 'evidence-based' clinical practice guidelines recommend the use of red flags to screen for serious causes of back pain.However, it remains unclear if the diagnostic accuracy of red flags is sufficient to support this recommendation.
Gesehen am 15.11.2021